Willingness of women‐led businesses in Pakistan to join formal e‐commerce platforms. Issue 3 (15th November 2022) - Hasan, Syed M.; Mustafa Khan, M. Raza; Arif, Verda
Abstract: An equitable distribution of economic benefits from the recent growth of e‐commerce in Pakistan requires inclusive adoption of formal digital marketplaces. The available literature and focused discussions reveal that most women‐led businesses rely on informal e‐commerce managed through social media applications and have incomplete and often incorrect information on the benefits and choices related to the formal platforms. To inform and motivate women‐led micro, small and medium enterprises, this study deploys an information treatment through a randomised control trial of 300 women entrepreneurs in large urban centres of Pakistan. Results show that women entrepreneurs were responsive to the information, as the treated businesses were 10 percentage points more likely to opt for formal e‐commerce than the control group. The study is policy relevant as the methodology allows simple and inexpensive replication to scale up the treatment for better business growth for women entrepreneurs in Pakistan.